Defining European Union’s Energy Security from the Perspective of 4A (Availability, Accessibility, Acceptability, Affordability) as an Impact from Russia-Ukraine’s Conflict - Budiman, Nuans Asa S; Ramadhan, Iqbal (Journal of International Relations on Energy Affairs, 2024)
Energy issues become one of dilemma of European Union in Rusia invasion to Ukraine.  The author of this scientific study analyzes European Union policy using Benjamin Sovacool's idea of energy security, including availability, accessibility, acceptability, and affordability. To explore this phenomenon, the author used qualitative research techniques and internet-based research. This study demonstrates how the European Union is putting numerous policies into practice to reduce energy scarcity by seeking out nations that can cooperate with them in the production of oil and gas, like Algeria, Qatar, and Norway. The European Union is also building a network of infrastructure for the distribution of gas and oil so that people in the area may access and affordably buy energy sources. By maximizing renewable energy, the European Union is diversifying its energy mix and reducing its reliance on imports of gas and oil.